Understanding the haematopoietic differentiation potential of human pluripotent stem cells - French, A; Anna L French (2013)
Pluripotent stem cells (PSCs), both embryonic stem (ES) and induced pluripotent stem (iPS) cells, have the capacity to generate any cell type of the body and therefore have application in disease modelling, as a drug-screening tool and as a cell source for regenerative medicine. The development of the human haematopoietic system can be investigated within a PSC differentiation system, which has been demonstrated to faithfully recapitulate aspects of haematopoietic ontogeny. Furthermore, PSC-derived haematopoietic cells may be a viable alternative, in a clinical setting, to cells isolated from bone marrow, peripheral blood or umbilical cord blood. iPS cells, which can be generated from a multitude of adult somatic tissues, have a number of advantages over ES cells, that include ethical and immunogenic implications. The aim of this thesis was to investigate the capacity of human iPS cells to give rise to B lymphocytes, an output that has challenged the field. In the context of haematopoietic differentiation from PSCs, the generation of lymphocytes provides a valuable readout that is synonymous with the definitive waves of haematopoiesis and that could be used as a disease model for numerous leukaemias. Here, B lymphocytes were robustly generated from iPS cells. These iPS-derived B cells showed a high level of similarity at the global transcriptional level with B cells generated from UCB haematopoietic stem/progenitor cells. The cellular origins of iPS-derived B cells were investigated and it was demonstrated that a putative haemogenic endothelial population could generate B lymphocytes with an 80- fold enrichment in this potential, when compared to haematopoietic progenitor fractions. Finally, the capacity of iPS-derived B cells to generate cell surface immunoglobulins has been described for the first time. Interestingly, the production of these IgM+ cells was inhibited by the addition of recombinant IL-7.